2016
DOI: 10.1186/s12959-016-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis of hemophilia A

Abstract: Preimplantation genetic diagnosis (PGD) is a powerful tool to tackle the transmission of monogenic inherited disorders in families carrying the diseases from generation to generation. It currently remains a challenging task, despite PGD having been developed over 25 years ago. The major difficulty is it does not have an easy and general formula for all mutations. Different gene locus needs individualized, customized design to make the diagnosis accurate enough to be applied on PGD, in which the quantity of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Therefore, this new panel improves the odds of identifying markers that are informative for use in standalone indirect linkage analysis, or as a complement to direct mutation detection, in couples wishing to undergo PGD for HEMA. Several reports have demonstrated that multiplex marker PCR is a reliable indirect linkage-based PGD method for cases involving inversion mutations [19][20][21][22]. Hence, this tetradecaplex marker panel, which contains more markers than previously reported panels, is likely to benefit carriers of the intron-1 or intron-22-mediated inversion mutations the most, because direct single-cell mutation detection is not possible and indirect linkage analysis is the only option [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this new panel improves the odds of identifying markers that are informative for use in standalone indirect linkage analysis, or as a complement to direct mutation detection, in couples wishing to undergo PGD for HEMA. Several reports have demonstrated that multiplex marker PCR is a reliable indirect linkage-based PGD method for cases involving inversion mutations [19][20][21][22]. Hence, this tetradecaplex marker panel, which contains more markers than previously reported panels, is likely to benefit carriers of the intron-1 or intron-22-mediated inversion mutations the most, because direct single-cell mutation detection is not possible and indirect linkage analysis is the only option [19].…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers, also referred to as short tandem repeats (STRs), have been widely used in linkage analysis as they are highly polymorphic and widespread within the human genome. A list of STRs located in and around the F8 gene has been reported previously [10], some of which have been multiplexed in small panels [9,[11][12][13][14][15][16][17][18][19][20][21][22]. However, a majority of these STRs have not been tested experimentally and their heterozygosity and polymorphism indices are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations c.5587-93C>T and c.5999-277G>A were identified by in-vitro assays using pcDNA 3.1/V5-His-TOPO vector [ 28 ]. To our knowledge, this was the first report using pSPL3 plasmids as the vectors in identifying splice mutations of F8 gene, and it provided another further verification method in genetic, prenatal diagnosis and preimplantation genetic diagnosis of hemophilia A [ 29 ]. The pSPL3 exon trapping vector contains two exons SD and SA, and a functional intron, with transcription beginning following the SV40 promoter and ending at the late poly (A) signal [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 If available, preimplantation genetic diagnosis (PGD) identifies unaffected embryos, yet has limitations. 17 Chorionic villus sampling and amniocentesis may be offered to interested carriers; these should be performed at knowledgeable centres due to a 1%-2% associated risk of miscarriage. 15,18 If diagnosis is not established before delivery, sex determination via ultrasound and cord blood testing at birth for male infants are recommended.…”
Section: Op Timal B Leed Pre Venti On: Defining the Op Timal Haemosmentioning
confidence: 99%